2020
DOI: 10.1074/jbc.ra119.012347
|View full text |Cite
|
Sign up to set email alerts
|

Oversized ubiquinones as molecular probes for structural dynamics of the ubiquinone reaction site in mitochondrial respiratory complex I

Abstract: NADH-quinone oxidoreductase (complex I) couples electron transfer from NADH to quinone with proton translocation across the membrane. Quinone reduction is a key step for energy transmission from the site of quinone reduction to the remotely located proton-pumping machinery of the enzyme. Although structural biology studies have proposed the existence of a long and narrow quinone-access channel, the physiological relevance of this channel remains debatable. We investigated here whether complex I in bovine heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 67 publications
1
32
0
Order By: Relevance
“…Taken together, the action mechanisms of complex I inhibitors with widely different chemical frameworks are far more diverse than hitherto considered based on the channel model (13,40,47,48). We recently demonstrated that complex I in bovine SMPs can catalytically reduce oversized ubiquinones, which are highly unlikely to transit the narrow channel because their side chain includes a significantly bulky block (30,49). This fact may question whether the current channel model fully reflects the physiologically relevant states.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the action mechanisms of complex I inhibitors with widely different chemical frameworks are far more diverse than hitherto considered based on the channel model (13,40,47,48). We recently demonstrated that complex I in bovine SMPs can catalytically reduce oversized ubiquinones, which are highly unlikely to transit the narrow channel because their side chain includes a significantly bulky block (30,49). This fact may question whether the current channel model fully reflects the physiologically relevant states.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquinone binding to complex I has also been explored using synthesized ubiquinone derivatives of varying lengths, with bulky groups (1-methoxy-2,6-di(3-methoxy-3-methyl-1-butynyl)benzene) added to the end of their tails—known as ‘oversized ubiquinones’ (OS-UQs). The bulky group is too large to pass through the entrance to the ubiquinone-binding channel from the membrane, and if the linking tail is not long enough, the ubiquinone headgroup is unable to reach its catalytic site at the end of the channel ( 51 , 52 ). Bovine complex I reconstituted into proteoliposomes was only able to catalyze the inhibitor-sensitive reduction of OS-UQ8, which has a tail length equivalent to eight isoprenoid units, predicted by the structure to be just long enough.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the evidence for a single narrow Q access pathway in complex I seems to be compelling. However, it should be noted that Uno et al (2020) showed inhibitor-sensitive reduction of Q analogs which are too bulky to enter the Q tunnel. It is currently unclear how these results can be reconciled with the structural data and more work is needed to resolve this issue.…”
Section: The Q Reduction Site and The Access Pathway For The Substrate From The Membranementioning
confidence: 98%